2013
DOI: 10.1108/10878571311323163
|View full text |Cite
|
Sign up to set email alerts
|

Three proven rules: discovering how exceptional companies think

Abstract: hat is the secret of long-term exceptional corporate performance? There have been many attempts to answer this question, but satisfying prescriptions remain elusive. Previous efforts typically succumb to one or both of two flaws. First, they fail to identify truly exceptional companies and end up studying ''lucky random walkers.'' Second, their advice is frequently vacuous when boiled down to statements such as ''get the right people on the bus,'' as if getting the wrong people on the bus was ever an objective… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Yet as incumbents fail to detect disrupters, it offers even greater opportunities for disrupters to build further capabilities to not only target customers in the lower-end market segments, but also the mainstream customers that are considered as the most profitable by the incumbents. As they undertake such initiatives, they tend to preserve advantages such as cost control and capabilities to offer superior qualities that influenced their initial success (Raynor & Mumtaz, 2013). The implications of these are often latent in the fact that disruption tends to occur when a significant number of the customers in the incumbents' most profitable segments begin to embrace the disrupter's offerings.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet as incumbents fail to detect disrupters, it offers even greater opportunities for disrupters to build further capabilities to not only target customers in the lower-end market segments, but also the mainstream customers that are considered as the most profitable by the incumbents. As they undertake such initiatives, they tend to preserve advantages such as cost control and capabilities to offer superior qualities that influenced their initial success (Raynor & Mumtaz, 2013). The implications of these are often latent in the fact that disruption tends to occur when a significant number of the customers in the incumbents' most profitable segments begin to embrace the disrupter's offerings.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In such cases, disruptive innovations may not only cause declining sales, revenues, profitability and returns on shareholders' value, but also a firm's probable exit. That implies constant analysis and devising of the strategies for dealing with disruptive innovations are prerequisites for leveraging a business' overall sustainability (Raynor & Mumtaz, 2013). Unfortunately, research and development of the theories for dealing with disruptive innovations remain largely premature for businesses to identify any meaningful business models that can be replicated to counter threats from disruptive innovations.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Research conducted after Campbell-Hunt's comprehensive review but using the dimensional approach to strategy he recommends has done little to resolve the debate (Leitner & Güldenberg, 2010;Spanos et al, 2004). Research by Raynor and Ahmed (2013) found that pure differentiation strategies are the most likely to yield sustained levels of exceptional profitability, and pure costbased positions (insofar as they are made manifest through competitive positions reliant on price leadership) are the least likely to do so, with hybrid positions enjoying intermediate probabilities of exceptional longterm results. Interestingly this work controls for the relationship between returns and longevity when calculating its relative measure of corporate performance.…”
Section: Strategy and Performancementioning
confidence: 99%